2020
DOI: 10.1186/s12877-020-1474-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mirabegron on cognitive function in elderly patients with overactive bladder: MoCA results from a phase 4 randomized, placebo-controlled study (PILLAR)

Abstract: Background: Antimuscarinics are often used for treatment of overactive bladder (OAB), but exposure to medications such as antimuscarinics that have anticholinergic properties has been linked to adverse cognitive effects. A phase 4 placebocontrolled study (PILLAR; NCT02216214) described the efficacy and safety of mirabegron, a β 3 -adrenoreceptor agonist, for treatment of wet OAB in patients aged ≥65 years. This pre-planned analysis aimed to measure differences in cognitive function between mirabegron and place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 63 publications
0
50
0
1
Order By: Relevance
“…TEAEs were assessed overall and in each age subgroup (< 75 and ≥ 75 years). TEAEs of special interest included cardiovascular events, blood pressure, myocardial infarction, stroke, serious arrhythmias, urinary tract infection (UTI), acute urinary retention, benign prostatic obstruction (BPO) requiring surgery, and cognitive impairment as determined by the Montreal Cognitive Assessment score (results presented in a separate manuscript [22]). Cardiovascular events were assessed by an independent adjudication committee.…”
Section: Methodsmentioning
confidence: 99%
“…TEAEs were assessed overall and in each age subgroup (< 75 and ≥ 75 years). TEAEs of special interest included cardiovascular events, blood pressure, myocardial infarction, stroke, serious arrhythmias, urinary tract infection (UTI), acute urinary retention, benign prostatic obstruction (BPO) requiring surgery, and cognitive impairment as determined by the Montreal Cognitive Assessment score (results presented in a separate manuscript [22]). Cardiovascular events were assessed by an independent adjudication committee.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with mirabegron over 12 weeks had no adverse impact on cognitive function in older patients at risk of or concerned with cognitive impairment, based on the Montreal Cognitive Assessment. 32 Therefore, mirabegron is increasingly being used as an alternative, especially to anticholinergic treatment in elderly patients. 5 …”
Section: Treatmentmentioning
confidence: 99%
“…The authors argue that combination therapy may be better for the elderly rather than solifenacin 10 mg, as the latter may increase the anticholinergic load. Another study found that there was no significant change in the Montreal Cognitive Assessment from baseline to week 12 in elderly patients using mirabegron 16 .…”
Section: Anticholinergic Loadmentioning
confidence: 99%